Effect of Environmental, Social, and Governance Disclosures on Organizational Visibility: Empirical Study of Non-Financial Companies Listed on the Indonesia Stock Exchange - Rizki Chairani; Zuraida Zuraida (Indonesian Journal of Sustainability Accounting and Management, 2021)
This study investigates the effect of environmental, social, and governance (ESG) disclosures on the organizational visibility of 25 non-financial companies listed on the Indonesia Stock Exchange (IDX) during the period of 2015–2019. We posit that ESG disclosure generally affects these firms positively. Our sample consists of 125 firm-year observations of the companies’ sustainability reports, as well as their coverage in the form of news and articles produced by national media. We measure visibility based on the number of media reports received by each of these corporations. Their ESG performances are scored according to the index issued by the Indonesian Ministry of Environment and Forestry. We employed multiple linear regression analysis to test our hypothesis. Our research demonstrates significant positive effects of the ESG in the aggregate and in the individual component of disclosures on organizational visibility. These results align with both the legitimacy theory in recognizing the social contract between a business and society and the stakeholder theory in acknowledging the relationships between a business and its customers, suppliers, investors, and others. Both theories underline and emphasize the importance of organizational behavior for ESG activities. Our study contributes to the vibrant and extensive ongoing debates in the organizational visibility literature regarding corporate ESG disclosure.